Nightsongs - Bert, Ari; Long, Loren (USA, 2012)
Chiro, a young bat, is nervous about flying into the world for the first time without his mother, especially on a very dark night, but he soon learns to rely on his song to find his way and stay safe...
Keywords: Animal - Bats; Juvenile Fiction; Mammals